Sintesis Selulosa Asetat dari Ampas Tebu sebagai Bahan Baku Biodegradable Foam - Meidini Suci Anjarwati; Anerasari Meidinariasty; Muhammad Yerizam (Fakultas Teknik, 2023)
The high cellulose content of bagasse allows it to be developed into a variety of valuable products, one of them is cellulose acetate which will be used to make biodegradable foam. The purpose of this research is to determine the best conditions for the synthesis of cellulose acetate from bagasse and test how cellulose acetate can be used to make biodegradable foam. This study used phosphoric acid as a solvent and glacial acetic acid as an acetylating agent to make cellulose acetate through the acetylation process. The variations in acetylation time in this study were 15, 30, and 45 minutes and the volume of glacial acetic acid as acetylating agent was 20, 40, 60, 80, and 100 ml. The results of this study indicated that the optimum conditions for the synthesis of cellulose acetate are 15 minutes of acetylation with a volume of 100 ml of glacial acetic acid, with a yield of 79.31% cellulose acetate, 36.19% acetyl content and a degree of substitution of 2.11. The test for the application of cellulose acetate to make biodegradable foam obtained a water absorption of 18.81%, the biodegradation test obtained was 24.53% in 14 days. In the biodegradable foam leak test for 10 minutes, no leakage occurred. This indicated that the biodegradable foam obtained was suitable to use because it complied with SNI.